1997
DOI: 10.1002/jpln.19971600211
|View full text |Cite
|
Sign up to set email alerts
|

Microbial biomass and N mineralization in relation to N supply of sugar beet under reduced tillage

Abstract: Reduced tillage may affect N supply of plants by influencing soil microbial biomass and thereby N release. The aim of this study was to evaluate changes in microbial biomass due to tillage in relation to N mineralization and to assess the contribution to the N supply of sugar beet. For this purpose, in a field trial near Göttingen in 1995 microbial biomass and net N mineralization were determined in an in situ incubation of ploughed and reduced tilled soil in plots which were not given application of mineral N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…The quality development at individual sites may differ from the average owing not only to weather conditions, but also to nitrogen availability. Despite the strong dependence of N mineralization on water availability and temperature 41. nitrogen availability may be a potential cause of the lack of correlation between the summer and autumn values of α‐amino nitrogen and total soluble nitrogen, although on average the concentrations were nearly constant after July.…”
Section: Discussionmentioning
confidence: 99%
“…The quality development at individual sites may differ from the average owing not only to weather conditions, but also to nitrogen availability. Despite the strong dependence of N mineralization on water availability and temperature 41. nitrogen availability may be a potential cause of the lack of correlation between the summer and autumn values of α‐amino nitrogen and total soluble nitrogen, although on average the concentrations were nearly constant after July.…”
Section: Discussionmentioning
confidence: 99%
“…Although N immobilization can result in reduced yields (Deenik et al, 2010), in a wet season such as the March -June period in this study, it probably mitigated NO 3 leaching potential, which possibly resulted in higher N efficiency. However, from a long-term field trial in Gottingen, Hoffmann et al (1997) concluded that minimal tillage systems increased Nnet mineralisation compared with conventional tillage systems, mainly due to the greater microbial biomass under reduced tillage. More research is therefore required to determine the factor(s) with overriding effects on sewage sludge N mineralization under Botswana conditions for development of sewage sludge management guidelines on agricultural soils.…”
Section: Seasonmentioning
confidence: 99%
“…Changes in C mjc / Corg are usually related with organic matter or microbial activity. Higher Cmlc/ Corg ratio is indicative of the decomposition of organic matter (Hoffmann et al , 1997) while lower C m« / Corg ratio, low-level and stable microbial activities ( Beyer et al , 1999) . Our results show that higher C mic / Corg values in roadside soils reflect depletion in soil organic matter and unstability in soil microbial activities.…”
Section: Microbial Ecophysiological -Parametersmentioning
confidence: 99%